A facile method to synthesize [A′(D′AD)2]-based push–pull small molecules for organic photovoltaics1. Issue 81 (3rd September 2015) - Shaker, Mohamed; Lee, Jong-Hoon; Trinh, Cuc Kim; Kim, Wonbin; Lee, Kwanghee; Lee, Jae-Suk
<x xml:space="preserve">Abstract</x> Synthesis of promising new composition low band gap small molecules based on the push–pull (donor–acceptor) system, which displayed power conversion efficiency of up to 3.24%.